Relaksasi Otot Progresif Pada Klien Diabetes Mellitus Dengan Masalah Keperawatan Ansietas (Studi Kasus) - Yana Karina; Esti Widiani2 (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
Diabetes Mellitus is an increase in blood sugar levels (hyperglycemia), this disease causes anxiety problems for sufferers. The purpose of this study was to determine progressive muscle relaxation in helping to overcome anxiety in people with diabetes mellitus. This research method is a case study design with a nursing process approach which includes assessment, data analysis, nursing diagnoses, planning, implementation and evaluation. Based on the results of the study after being given the patient's anxiety intervention decreased to the range of mild anxiety response. Provision of progressive muscle relaxation therapy interventions, can reduce susceptible anxiety response to the client and progressive muscle relaxation can also be used for diabetics who experience gangrene with the condition of avoiding the vulnerable parts of injury when making movements. Suggestions for nursing staff are expected to continue and find other nonpharmacological therapies for patients with diabetes mellitus with anxiety problems.